2018
DOI: 10.2478/fhort-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in phenolic compounds, biochemical and pomological characteristics of Arbutus unedo fruits

Abstract: Strawberry trees (Arbutus unedoL.) are naturally grown in particular Black Sea and Mediterranean regions of Turkey with great diversity due to continuous seed propagation for centuries. The trees differ in terms of most of the horticultural characteristics. We investigated the phenolic compounds and the biochemical and pomological characteristics of the fruits of eight strawberry tree selections naturally grown in the western part of Turkey. Significant differences were found among the genotypes in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
10
17
0
Order By: Relevance
“…The third component represents 13.87% of the total variation, which is defined essentially by total phenols (0.57), condensed tannins (0.77), total anthocyanins (0.80), cyanidin-3-glucoside (0.64), and cyanidin-3-arabinoside (0.64). Generally, these results were in accordance with those reported in previous strawberry tree biochemical studies [ 30 , 33 ]. They have reported that the biochemical attributes are important in order to evaluate the variation in traits of strawberry tree genotypes.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The third component represents 13.87% of the total variation, which is defined essentially by total phenols (0.57), condensed tannins (0.77), total anthocyanins (0.80), cyanidin-3-glucoside (0.64), and cyanidin-3-arabinoside (0.64). Generally, these results were in accordance with those reported in previous strawberry tree biochemical studies [ 30 , 33 ]. They have reported that the biochemical attributes are important in order to evaluate the variation in traits of strawberry tree genotypes.…”
Section: Resultssupporting
confidence: 93%
“…Generally, these results were in accordance with those reported in previous strawberry tree biochemical studies [ 30 , 33 ]. These studies indicated that high diversity in biochemical traits could be used as an efficient marker system to discriminate between strawberry tree genotypes, comparing our results to other fruits such as sweet cherry [ 44 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The value of ABTS assay ranged from 2.25 to 19.58 mg ascorbic acid equivalent/g DW. Gündogdu et al [56] and Colak [20] recorded the antioxidant capacity (ABTS) values ranged between 17.51 and 30.06 µmol TE/g DW and between 18.07 and 33.41 µmol TE/g DW in Turkish A. unedo fruits. This difference was most probably due to differences in the extraction method and solvent used.…”
Section: Antioxidant Activitiesmentioning
confidence: 98%
“…Antioxidant activity was widely studied on strawberry tree fruits by using different antioxidant determining methods such as ABTS, TEAC, FRAP, DPPH, etc., and all studies indicated that A. unedo fruits had high antioxidant activity and antioxidant activity found to be genotype dependent. Moreover, the studies indicated that type of extraction of phenols present in fruits of A. unedo also influenced the antioxidant activity [7,8,14,39,[51][52][53]55,56]. In addition, several reports showed that strawberry tree fruit is a highly potential antioxidant plant compared to other fruit, such as red and green grape and apples [57], pomace [58], pomegranate [59], grape [60,61], which can be linked to the high phenolic composition of strawberry tree fruits in polyphenols.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%